Optimisation of high efficiency tin halide perovskite solar cells using SCAPS-1D. (2018) - Mandadapu, Usha; Vedanayakam, S. Victor; Thyagarajan, K.; Babu, B.J.
Hybrid perovskite solar cells are creating attention due to the enormous growth of efficiency exceeding 20%, indicating in near future these cells will become an alternative to the traditional silicon photovoltaics. For the commercialisation of low-cost, high efficiency perovskite solar cells, better investigation of the relation between the various material parameters, the device architectures and power conversion efficiency (PCE) of the device is needed. Three types of architectures are designed and simulated using the solar cell capacitance simulator (SCAPS-1D), used for the analysis of thin film photovoltaic architecture. One architecture is Glass/ZnO:Al/TiO2 /CH3 NH3 SnI3 /Au, second one is Glass/TiO2 /ZnO:Al/CH3 NH3 SnI3 /CuI/Au and Glass/ZnO:Al/TiO2 /CH3 NH3 SnI3 /CH3 NH3 SnBr3 /CuI/Au is the architecture of third model. Analysis was done by studying the various material parameters effect on the device performance. It was observed that the second one [model (2)] showed the maximum PCE of 25.91%. This simulation work is useful to the researchers in the design of low cost, non-toxic, high efficiency tin halide perovskite solar cells.